2021
DOI: 10.3389/fgene.2021.754198
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress Alters Gene Expression and Cytoarchitecture in the Prefrontal Cortex Leading to Social Impairment and Increased Anxiety

Abstract: Early life stress (ELS), such as abuse, neglect, and maltreatment, exhibits a strong impact on the brain and mental development of children. However, it is not fully understood how ELS affects social behaviors and social-associated behaviors as well as developing prefrontal cortex (PFC). In this study, we performed social isolation on weaned pre-adolescent mice until adolescence and investigated these behaviors and PFC characteristics in adolescent mice. We found the ELS induced social impairments in social no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Along these lines, studies have shown that microglia are also more broadly impacted in rodent models of ELA. Maternal separation during the early postnatal period, as well as social isolation during adolescence, alters microglia morphology, activation, and number in the hippocampus and prefrontal cortex ( Delpech et al, 2016 ; Bachiller et al, 2020 ; Gildawie et al, 2020 ; Reshetnikov et al, 2020 ; Usui et al, 2021 ), and some evidence suggests that ELA-induced increases in microglial activation may be responsible for some of its effects on stress vulnerability, including reduced reward seeking and stress coping after subsequent stress exposure. Given the important role that microglia play in synaptogenesis, synapse elimination, and synaptic plasticity ( Wu et al, 2015 ; Wilton et al, 2019 ), it seems likely that microglial activation might be causally linked to ELA-induced behavioral phenotypes.…”
Section: Cellular Effects Of Early Life Adversity: Similarities and D...mentioning
confidence: 99%
“…Along these lines, studies have shown that microglia are also more broadly impacted in rodent models of ELA. Maternal separation during the early postnatal period, as well as social isolation during adolescence, alters microglia morphology, activation, and number in the hippocampus and prefrontal cortex ( Delpech et al, 2016 ; Bachiller et al, 2020 ; Gildawie et al, 2020 ; Reshetnikov et al, 2020 ; Usui et al, 2021 ), and some evidence suggests that ELA-induced increases in microglial activation may be responsible for some of its effects on stress vulnerability, including reduced reward seeking and stress coping after subsequent stress exposure. Given the important role that microglia play in synaptogenesis, synapse elimination, and synaptic plasticity ( Wu et al, 2015 ; Wilton et al, 2019 ), it seems likely that microglial activation might be causally linked to ELA-induced behavioral phenotypes.…”
Section: Cellular Effects Of Early Life Adversity: Similarities and D...mentioning
confidence: 99%
“…Nevertheless, previous studies showed multivariate results of the cortex in PTSD models. In an early-life stress and herpes zoster pain model, microglia in the PFC is markedly activated ( Ma et al, 2021 ; Usui et al, 2021 ). Neuroinflammation originating from microglia in the medial PFC induced by chronic stress, leading to depressive-like behavior ( Kitaoka, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR (qPCR) was performed as described previously ( 16 , 21 ). Total RNA was extracted from the mouse prefrontal cortex (PFC) using the miRNeasy Mini Kit (#217004; Qiagen, Hilden, Germany) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%